State of Health Battery Estimation by Using the OCPP of Charging Station Combined with Loss of EV Charging System - Peanjad, Pannawat; Khomfoi, Surin; Phophongviwat, Teeraphon; Manee-Inn, Chaitouch; Thounthong, Phatiphat (My University, 2023)
The research paper focuses on estimating the health of electric vehicle batteries using electrical variables measured by the charger during the charging process. These variables are sent to a central processing system via OCPP (Open Charge Point Protocol), as the charger itself has limitations in directly measuring battery health. To overcome this limitation, this research utilizes electrical variables measured by the DC charger during the charging process to estimate battery health. The Coulomb counting method is employed in combination with an investigation into losses within the vehicle's charging system to enhance the accuracy of State of Health (SoH) estimation. The obtained battery health values will assist electric vehicle users in better trip planning and maintenance scheduling.
Keywords: coulomb counting method; Open Charge Point Protocol OCPP; State of health(SoH)